2009
DOI: 10.1167/iovs.08-1960
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Effects of Intraocular Pressure Elevation on Optic Nerve/Lamina Cribrosa before and after Peripapillary Scleral Collagen Cross-Linking

Abstract: Stiffening of the peripapillary scleral ring reduces the biomechanical sensitivity of the ON/LC complex to IOP elevation and may represent a novel mechanism for neuroprotection in glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 31 publications
2
44
0
2
Order By: Relevance
“…Zeimer et al [41] observed a decrease in ONH compliance in 15 human glaucomatous postmortem eyes while the visual field worsened indicating a stiffening of the mechanical support of the ONH. However, there is also evidence that stiffening, especially of the ppSc, might represent a compensatory response involving an attempt by the ECM to resist the increased stress and strain imposed by elevated IOP in disease predisposition but not in early induced glaucoma models [42,43] .…”
Section: Discussionmentioning
confidence: 99%
“…Zeimer et al [41] observed a decrease in ONH compliance in 15 human glaucomatous postmortem eyes while the visual field worsened indicating a stiffening of the mechanical support of the ONH. However, there is also evidence that stiffening, especially of the ppSc, might represent a compensatory response involving an attempt by the ECM to resist the increased stress and strain imposed by elevated IOP in disease predisposition but not in early induced glaucoma models [42,43] .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to riboflavin activated by ultraviolet light (Wollensak et al, 2003) or glyceraldehyde (GA) treatment (Thornton et al, 2009;Wollensak and Iomdina, 2008) stiffen the cornea and sclera, altering their stress-strain behavior without significant damage to the retina or other ocular structures. To test this approach, we produced experimental IOP elevation in CD1 mice after three subconjunctival injections of 0.5 M GA.…”
Section: Therapy Involving the Noncellular Componentsmentioning
confidence: 99%
“…Viscoelastic tensile creep and relaxation tests have also been conducted on these tissues [21,[23][24][25]. Inflation tests wherein whole [19,[26][27][28][29][30][31] or partial globes [32][33][34][35][36][37] are subjected to increasing levels of pressure while the scleral surface is imaged have been used to study the sclera's strain field, viscoelasticity, and the effects of various eye disease treatments. In general, these types of tests, particularly those on whole globes, are more physiologically realistic than tests on excised specimens.…”
Section: Introductionmentioning
confidence: 99%